O nível de esforço físico durante o treinamento coletivo no Futsal na categoria Sub 13 - Mendes, Cristian Jiacomin Redondo [UNESP] (Universidade Estadual Paulista (Unesp), 2011)
Futsal is one of the most popular sports in Brazil, played on five continents, in hundreds of countries, but is still a poorly studied sports science. Among the types of training used in the preparation of soccer players, the collective training is one of the most used because it is a simulation game. The application of the training load is often made in large quantities (volume) with exercise duration and intensity greater than what the athlete can handle. Thus, this study aimed to evaluate the intensity of physical exertion of futsal players of basic category during collective training. We evaluated twenty (N=20) soccer players from two teams with different levels of training. There were ten players on a team federated (FED) and ten players on a team for a project extension (EXT). Samples were collected at the respective locations of training. An evaluation of anthropometric and during collective training heart rate was measured and at the end of each training time blood samples were collected for analysis of blood lactate concentration and perceived exertion of the players. There was significant difference between the two teams only in fat percentage (FED=13,4 e EXT=21,2). The average heart rate during training was 174 ± 12.2 bpm, which corresponds to 84% HRmax. There was significant difference between heart rate and the percentage of HRmax in the two parts of training in both teams. The Federated team players remained most of the time in more intense intensity zone (above 85% HRmax), while the EXT players were most of the time zone of moderate intensity (65-85% HRmax). The rating of perceived exertion (FED=3,5 e EXT=3,2) and blood lactate concentration (FED=2.4 mmol/L and EXT=2.9 mmol/L) showed no significant difference between the two teams and between the two times. During training there was a significant correlation (p= 0.71) between heart rate and lactate concentration. The collective training showed an intensity that is supposed to be...

O futsal é um dos esportes mais populares do Brasil, praticado nos cinco continentes, em centenas de países, mas, ainda é um esporte pouco estudado cientificamente. Dentre os tipos de treinamento utilizados na preparação dos jogadores de futsal, o treinamento coletivo é um dos mais utilizados, por ser uma simulação do jogo. A aplicação da carga de treinamento muitas vezes é feita em grande quantidade (volume) de exercícios com duração e intensidade superiores ao que o atleta pode suportar. Deste modo, o presente estudo teve como objetivo avaliar a intensidade de esforço físico de jogadores de futsal da categoria de base durante o treinamento coletivo. Foram avaliados vinte (N=20) jogadores de duas equipes futsal com diferentes níveis de treinamento. Foram dez jogadores de uma equipe federada (FED) e dez jogadores de uma equipe de um projeto de extensão (EXT). As coletas foram realizadas nos respectivos locais de treinamento. Foi realizada uma avaliação antropométrica e durante o treinamento coletivo foi aferida a freqüência cardíaca e, ao término de cada tempo do treinamento foram coletadas amostras de sangue para análise da concentração sanguínea de lactato e a percepção subjetiva de esforço dos jogadores. Houve diferença significante entre as duas equipes apenas no percentual de gordura (FED=13,4 e EXT= 21,2). A média da freqüência cardíaca durante o treinamento foi de 174 ± 12,2 bpm, o que corresponde a 84% da FCmax. Houve diferença significante entre a freqüência cardíaca e o percentual da FCmax nas duas partes do treinamento, em ambas as equipes. Os jogadores da equipe federada permaneceram a maior parte do tempo na zona de intensidade mais intensa (acima de 85% da FCmax), enquanto que os jogadores EXT ficaram a maior parte do tempo na zona de intensidade moderada (65-85% da FCmax). A percepção subjetiva de esforço (FED=3,5 e EXT= 3,2) e a concentração sanguínea de lactato (FED=2,4 mmol/L e...
Keywords: Percepção social nas crianças; Futebol de salão; Futebol de salão - Regras; Lactatos; Batimento cardíaco; Futebol - Treinamento; Social perception in children